(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Given the increasing importance of sustainability reporting, auditors must adapt their procedures to verify the accuracy and reliability of sustainability information. Therefore, understanding the implications of the economic indicators disclosed in the Global Reporting Initiative (GRI) standards on audit procedures is crucial for both auditors and companies to ensure the credibility of these reports. Therefore, the research aimed to measure the level of disclosure of economic indicators related to sustainability in the oil and gas sector in accordance with the standards of the Global Reporting Initiative (GRI) and its reflection in audit procedures. To achieve this, the research relied on the method of content analysis of financial reports and the Board of Directors’ report when measuring and testing the level of disclosure of the requirements of economic indicators for sustainability reports in the oil and gas sector, devising the audit procedures proposed by the Global Reporting Initiative (GRI) standards, and choosing the Basra Oil Company to apply the practical aspect and prove the hypotheses. search. One of the most important findings of the research was the decrease in the overall rating of the level of commitment of the Basra Oil Company (the research sample) to disclosing the economic standards of the Global Reporting Initiative (GRI) by (22.5%), in addition to the discrepancy in the level of disclosure of the economic indicators of sustainability reports according to the standards (GRI). The research also reached many recommendations, the most important of which is the need to oblige oil and gas sector companies operating in Iraq to apply the indicators and standards of the Global Reporting Initiative (GRI) to prepare sustainability reports and adopt the proposed audit program.